Optimalisasi Layanan Kesehatan Melalui Inovasi Pelayanan Publik Proyek Perubahan Pelatihan Kepemimpinan (Optimizing Health Services Through Public Service Innovation Project Change In Leadership Training) - Alih Aji Nugroho; Edy Sutrisno; Rima Ranintya Yusuf (Politeknik STIA LAN Bandung, 2020)
ABSTRACTOptimal public services are an absolute requirement for government administrators. Optimizing public services can be done through innovation, to bring services closer to the community, more accessible, higher quality, and cheaper. The application of innovation is expected to be able to make the products and services produced have added value, each individual is encouraged to work faster, more precisely and carefully, and innovation is expected to give birth to a better work culture. South Tangerang City is an autonomous region that was formed at the end of 2008, so there is a need to increase human resource capacity related to public service innovation. Direct services to the community that are quite highlighted are health services. On this basis, we conduct community service interventions in the form of workshops and mentoring to all heads of UPT South Tangerang City Health Office in order to further optimize service innovation. The workshop is devoted to leadership training alumni who already have innovations in the form of change projects. The activity is carried out between October-November 2019. Before conducting the workshop, identification of serviceÂ innovations has been carried out. As a result, the head of the UPT has a common perception and strategy to continue and develop public service innovations, especially the results of change projects.ABSTRAKPelayanan publik yang optimal menjadi syarat mutlak bagi penyelenggara pemerintah. Optimalisasi pelayanan publik dapat dilakukan melalui inovasi, untuk mendekatkan pelayanan kepada masyarakat, lebih mudah diakses, lebih berkualitas, dan lebih murah. Penerapan inovasi diharapkan mampu membuat produk barang dan jasa yang dihasilkan memiliki nilai tambah, setiap individu terdorong untuk bekerja lebih cepat, tepat dan cermat, serta inovasi diharapkan melahirkan budaya kerja yang lebih baik. Kota Tangerang Selatan merupakan daerah otonom yang terbentuk pada akhir tahun 2008, sehingga dibutuhkan peningkatan kapasitas SDM terkait inovasi pelayanan publik. Pelayanan langsung pada mayarakat yang cukup disorot adalah layanan kesehatan. Atas dasar tersebut kami melakukan interversi pengabdian berupa workshop dan pendampingan kepada seluruh kepala UPT Dinas Kesehatan Kota Tangerang Selatan agar lebih mengoptimalkan inovasi pelayanan. Workshop dikhususkan pada alumni pelatihan kepemimpinan yang sudah memiliki inovasi berupa proyek perubahan. Kegiatan dilakukan antara bulan Oktober-November 2019. Sebelum melakukan workshop, dilakukan identifikasi inovasi pelayanan yang telah dilaksanakan. Hasilnya, kepala UPT mempunyai persamaan persepsi dan strategi untuk melanjutkan dan mengembangkan inovasi pelayanan publik khususnya hasil proyek perubahan.Â